The flip side of sirtuins: the emerging roles of protein acetyltransferases in aging - Nagarajan, Prabakaran (Aging (Albany NY), 2020)
Protein N-ε-lysine acetylation is is an important post-translational modification that plays critical roles in the regulation of many cellular processes. A role for this modification in the process of aging goes back two decades to the discovery that the yeast NAD(+)-dependent histone deacetylase Sir2 regulates lifespan in yeast. While the Sirtuin family of protein deacetylases has been intensively studied in many model systems and is definitively linked to aging, the enzymes responsible for protein acetylation, protein acetyltransferases (KATs), have not received a similar level of attention. However, a series of recent studies have directly explored the role of specific KATs in aging. These studies have shown that modulation of KAT activity can influence cellular pathways important for aging and directly effect organismal lifespan.